A lead for integration of perinatal mental health in maternal and child health services - Pal, Monalisha (International Journal Of Community Medicine And Public Health, 2023)
Life altering moments like pregnancy, birth, and early parenthood can be stressful for women and their partners. As a result, women may undergo a period of poor mental health or witness a worsening of previous mental health or witness a worsening of previous mental health condition. Almost 1 in 5 women will experience a mental health condition during pregnancy or in the year after birth. Among women with perinatal mental health condition, 20% will experience suicidal thoughts or undertake acts of self-harm. Ignoring mental health not only risks women’s overall health and wellbeing, but also impacts infant’s physical and emotional development. This article is based on a comprehensive literature search conducted on 22 February 2023, in the Medline and Cochrane databases, utilizing the medical topic headings (MeSH) and a combination of all available related terms, according to the database. To prevent missing any possible research, a manual search for publications was conducted through Google Scholar, using the reference lists of the previously listed in papers as a starting point. I looked for valuable information in papers that discussed information about the classification, pathophysiology and principles of therapy of shock. There are no restrictions on date, language, participants, age, or type of publication.